The emergence and outgrowth of Business Process Outsourcing (BPO) industry in Bangladesh - Sagar, Nowshad Mohsin (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.